Lateral Resolution Enhancement of Vertical Scanning Interferometry by Sub-Pixel Sampling. (7th January 2014) - Arvidson, Rolf S.; Fischer, Cornelius; Sawyer, Dale S.; Scott, Gavin D.; Natelson, Douglas; Lüttge, Andreas
Abstract We apply common image enhancement principles and sub-pixel sample positioning to achieve a significant enhancement in the spatial resolution of a vertical scanning interferometer. We illustrate the potential of this new method using a standard atomic force microscope calibration grid and other materials having motifs of known lateral and vertical dimensions. This approach combines the high vertical resolution of vertical scanning interferometry and its native advantages (large field of view, rapid and nondestructive data acquisition) with important increases in lateral resolution. This combination offers the means to address a common challenge in microscopy: the integration of properties and processes that depend on, and vary as a function of observational length.